Empire of influence the East India Company and the making of indirect rule - Wilkinson, Callie 1990- (Cambridge University Press, 2023)
Indirect rule is widely considered as a defining feature of the nineteenth and twentieth century British Empire but its divisive earlier history remains largely unexplored. Empire of Influence traces the contentious process whereby the East India Company established a system of indirect rule in India in the first decades of the nineteenth century. In a series of thematic chapters covering intelligence gathering, violence, gift giving and the co-optation of the scribal and courtly elite, Callie Wilkinson foregrounds the disagreement surrounding the tactics of the political representatives of the Company and recaptures the experimental nature of early attempts to secure Company control. She demonstrates how these endeavours were reshaped, exploited and resisted by Indians as well as disputed within the Company itself. This important new account exposes the contested origins of these ambiguous relationships of 'protection' and coercion, while identifying the factors that enabled them to take hold and endure